Equivalence and duality for module categories (with tilting and cotilting for rings) - Colby Robert R; Fuller Kent R (Cambridge CUP, 2004)
This book provides a unified approach to much of the theories of equivalence and duality between categories of modules that has transpired over the last 45 years. In particular, during the past dozen or so years many authors (including the authors of thi
Keywords: Duality theory(Mathematics); Modules(Algebra); Rings(Algebra)